Transverse cardiac slicing and optical imaging for analysis of transmural gradients in membrane potential and Ca2+ transients in murine heart. (26th July 2018) - Wen, Q.; Gandhi, K.; Capel, Rebecca A.; Hao, G.; O'Shea, C.; Neagu, G.; Pearcey, S.; Pavlovic, D.; Terrar, Derek A.; Wu, J.; Faggian, G.; Camelliti, Patrizia; et al.
Abstract : Key points: A robust cardiac slicing approach was developed for optical mapping of transmural gradients in transmembrane potential ( V m ) and intracellular Ca 2+ transient (CaT) of murine heart. Significant transmural gradients in V m and CaT were observed in the left ventricle. Frequency‐dependent action potentials and CaT alternans were observed in all ventricular regions with rapid pacing, with significantly greater incidence in the endocardium than epicardium. The observations demonstrate the feasibility of our new approach to cardiac slicing for systematic analysis of intrinsic transmural and regional gradients in V m and CaT. Abstract: Transmural and regional gradients in membrane potential and Ca 2+ transient in the murine heart are largely unexplored. Here, we developed and validated a robust approach which combines transverse ultra‐thin cardiac slices and high resolution optical mapping to enable systematic analysis of transmural and regional gradients in transmembrane potential ( V m ) and intracellular Ca 2+ transient (CaT) across the entire murine ventricles. The voltage dye RH237 or Ca 2+ dye Rhod‐2 AM were loaded through the coronary circulation using a Langendorff perfusion system. Short‐axis slices (300 μm thick) were prepared from the entire ventricles (from the apex to the base) by using a high‐precision vibratome. Action potentials (APs) and CaTs were recorded with optical mapping during steady‐state baseline and rapid pacing. Significant transmural gradients in V m and CaT were observed in the left ventricle, with longer AP duration (APD50 and APD75 ) and CaT duration (CaTD50 and CaTD75 ) in the endocardium compared with that in the epicardium. No significant regional gradients were observed along the apico‐basal axis of the left ventricle. Interventricular gradients were detected with significantly shorter APD50, APD75 and CaTD50 in the right ventricle compared with left ventricle and ventricular septum. During rapid pacing, AP and CaT alternans were observed in most ventricular regions, with significantly greater incidence in the endocardium in comparison with epicardium. In conclusion, these observations demonstrate the feasibility of our new approach to cardiac slicing for systematic analysis of intrinsic transmural and regional gradients in V m and CaT in murine ventricular tissue. Key points: A robust cardiac slicing approach was developed for optical mapping of transmural gradients in transmembrane potential ( V m ) and intracellular Ca 2+ transient (CaT) of murine heart. Significant transmural gradients in V m and CaT were observed in the left ventricle. Frequency‐dependent action potentials and CaT alternans were observed in all ventricular regions with rapid pacing, with significantly greater incidence in the endocardium than epicardium. The observations demonstrate the feasibility of our new approach to cardiac slicing for systematic analysis of intrinsic transmural and regional gradients in V m and CaT.